2010
DOI: 10.5194/acp-10-2631-2010
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous nucleation of sulfuric acid and water mixture: experimental setup and first results

Abstract: Abstract. In this study we introduce a new flow tube suitable for binary and ternary homogeneous nucleation studies. The production of sulfuric acid and water vapor mixture, the experimental setup and the method of sulfuric acid concentration determination are discussed in detail. Wall losses were estimated from the measured sulfuric acid concentration profiles along the flow tube and compared to a theoretical prediction. In this investigation the experimental evidence of new particle formation was observed at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(114 citation statements)
references
References 29 publications
(45 reference statements)
9
103
1
1
Order By: Relevance
“…The detailed comparison to other literature data concerning sulfuric acid -water system is given in our previous publication Brus et al (2010), however the discrepancy was found in the results of this study compared to data published earlier . In our earlier study the method of bubblers was used to estimate concentration and the losses of sulfuric acid along the flow tube as the total sulfate (SO 2− 4 ) concentration obtained via ion chromatography (IC) analysis.…”
Section: Comparison To Our Previous Datacontrasting
confidence: 56%
See 1 more Smart Citation
“…The detailed comparison to other literature data concerning sulfuric acid -water system is given in our previous publication Brus et al (2010), however the discrepancy was found in the results of this study compared to data published earlier . In our earlier study the method of bubblers was used to estimate concentration and the losses of sulfuric acid along the flow tube as the total sulfate (SO 2− 4 ) concentration obtained via ion chromatography (IC) analysis.…”
Section: Comparison To Our Previous Datacontrasting
confidence: 56%
“…The wall loss factor (WLF) increases with relative humidity, which is due to presence of temperature gradient in first 50 cm in the nucleation chamber, see Brus et al (2010) for details. The presence of temperature gradient (both axial and radial) imposes thermophoretic force towards the cooled nucleation chamber wall (set to 25 • C) and also increases the value of diffusion coefficient, thus increasing WLF in first 50 cm.…”
Section: H 2 So 4 Lossesmentioning
confidence: 99%
“…Furthermore, binary diffusion coefficients of 0.09 cm 2 s −1 (H 2 SO 4 in air) and 0.06 cm 2 s −1 (H 2 SO 4 in H 2 O) were applied in the simulations (Marti et al, 1997;Hanson and Eisele, 2000;Brus et al, 2010). These values are comparable to values determined using the methods of Fuller (FSG, Fuller et al, 1966), FSG-LaBas (Lyman, 1990) or Wilcke and Lee (WL, Wilke and Lee, 1955), which yield 0.11 m 2 s −1 , 0.093 m 2 s −1 , respectively 0.1 m 2 s −1 .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The nucleation experiments were carried out in a laminar flow tube at the Finnish Meteorological Institute, Helsinki, Finland. The detailed description of the flow tube and the operational principle has been presented and discussed in detail by Brus et al (2010) and Neitola et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…At the outlet of the flow tube, the number concentrations of the produced particles were measured using an Ultrafine Condensation Particle Counter (UCPC, Model 3776, TSI Inc., USA). The same modification to UCPC TSI 3776 has been done previously, as described in Brus et al (2010), to obtain a d 50 cut-off of 2.25 nm. The saturator temperature was increased from a nominal 39 • C up to 40 • C, and the condenser temperature was decreased from a nominal 10 • C down to 8 • C. At these new temperatures no homogenous nucleation was observed inside the counter.…”
Section: Measurements and Experimental Set-upmentioning
confidence: 99%